Life transition stages of family caregivers for patients with chronic illness: A grounded theory study - Norfaezah Md Khalid; Nurul Salwa Sajali; Asbah Razali (Belitung Nursing Journal, 2025)
Background: Family caregivers play a crucial role in providing continuous support to individuals with chronic illnesses. Their responsibilities extend beyond the well-being of patients, influencing both patient health outcomes and their own. Caregiving entails significant responsibilities and sacrifices, requiring caregivers to navigate evolving roles and care needs over time. Existing literature highlights the emotional and psychological challenges faced by caregivers, including role transitions and stress. However, most studies focus on caregiving experiences rather than the specific transitional phases caregivers undergo after assuming their responsibilities.